1994
DOI: 10.1164/ajrccm.150.6.7952618
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of maximal flow-volume curves on time course of preceding inspiration in patients with chronic obstruction pulmonary disease.

Abstract: Thirteen patients with chronic obstructive pulmonary disease (COPD) performed forced vital capacity (FVC) maneuvers either immediately after a rapid inspiration (maneuver 1) or after a slow inspiration with a 4- to 6-s end-inspiratory pause (maneuver 2). Seated in a body plethysmograph, they breathed through a pneumotachograph. Inspirations were initiated from resting end-expiratory lung volume. Abdominal muscle activity was recorded by means of surface electrodes. With maneuver 1: (1) expiratory flows were 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 21 publications
6
20
0
Order By: Relevance
“…2. Indeed, it has been shown that even substantial differences in apparently maximal voluntary expiratory efforts play little or no role in COPD patients [5] and time dependency of FVC manoeuvres is also observed when lung volume changes are assessed plethysmographically [4,5]. The present results, in line with previous findings [4,6], suggest that loss of elastic recoil during breath-holding at full inspiration, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…2. Indeed, it has been shown that even substantial differences in apparently maximal voluntary expiratory efforts play little or no role in COPD patients [5] and time dependency of FVC manoeuvres is also observed when lung volume changes are assessed plethysmographically [4,5]. The present results, in line with previous findings [4,6], suggest that loss of elastic recoil during breath-holding at full inspiration, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…2 under baseline conditions 76% of patients could be classified as responders, whereas with the opposite combination the number would drop to 2%. These observations, which are in line with those performed on a small number of COPD and asthmatic patients in the laboratory [5,6], indicate that FVC manoeuvres before and after bronchodilator administration for the assessment of bronchodilator responsiveness must be made under standardised conditions even in the clinical setting under routine conditions. From a practical point of view, it is important to note that standardisation does not imply the choice of the type of manoeuvre.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations